2004
DOI: 10.2166/wh.2004.0001
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the health outcomes related to household water quality in developing countries

Abstract: In developing countries, the microbial contamination of household drinking water is implicated in the prevalence of various diseases. This systematic review is concerned with two health outcomes, general diarrhoea and cholera, and their relationship with water quality at point-of-use. Observational studies investigating this relationship are reviewed, as well as studies of home water treatment and storage interventions. For cholera, a clear relationship was found with contaminated water. Home water treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
157
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(168 citation statements)
references
References 31 publications
8
157
0
3
Order By: Relevance
“…Some research has shown an association between the consumption of highly contaminated water and diarrhea, 42,43 but other investigations have found no significant association between the level of fecal contamination in stored household drinking water and disease risk. [44][45][46][47] A recent systematic review and meta-analysis demonstrated an association between the detection-but not the amount-of E. coli contamination and diarrhea. 48 The considerable contamination of improved water sources observed in this and other studies demonstrates that the current MDG indicator for water quality should not be equated with safety.…”
Section: Discussionmentioning
confidence: 99%
“…Some research has shown an association between the consumption of highly contaminated water and diarrhea, 42,43 but other investigations have found no significant association between the level of fecal contamination in stored household drinking water and disease risk. [44][45][46][47] A recent systematic review and meta-analysis demonstrated an association between the detection-but not the amount-of E. coli contamination and diarrhea. 48 The considerable contamination of improved water sources observed in this and other studies demonstrates that the current MDG indicator for water quality should not be equated with safety.…”
Section: Discussionmentioning
confidence: 99%
“…27,31,32 For ceramic water filters, a POU technology comparable with the BSF because it is water treatment using a filter as a durable good rather than a consumable chemical disinfection treatment such as chlorine, diarrheal disease reductions between 29% and 72% have been reported. In an analogous post-implementation assessment of the pot-style ceramic water purifier in Cambodia using a prospective cohort study design, there was 46% lower diarrheal disease prevalence for filter household members compared with non-filter household members.…”
mentioning
confidence: 99%
“…Unsanitary methods of water serving from household storage vessels, including contaminated hands and dippers, and inadequate cleaning of vessels, which lead to accumulation of sediments and pathogens [10,15,16]. …”
Section: Resultsmentioning
confidence: 99%